Enhanced Two-Photon Fluorescence and Fluorescence Imaging of Novel Probe for Calcium Ion by Self-Assembly with Conjugated Polymer - Zhai, Yue-liang (Polymers (Basel), 2019)
The calcium ion (Ca(2+)) isa highly versatile intracellular signal messenger regulating many different cellular functions. It is important to design probes with good fluorescence and two-photon (TP) active cross-sections (Φδ) to explore the concentration distribution of Ca(2+). In this manuscript, a novel TP fluorescence calcium probe (BAPTAVP) with positive charges, based on the classical Ca(2+) indicator of BAPTA (1,2-bis(2-aminophenoxy)-ethane-N,N,N’,N’-tetra acetic acid), and a conjugated polymer (PCBMB) with negative charges were designed and synthesized. The results from transmission electron microscopy (TEM), atomic force microscopy (AFM), dynamic light scattering (DLS), and the zeta potential (ZP) showed that nanoparticles were obtained by the self-assembly of PCBMB and BAPTAVP. Moreover, the fluorescence properties of BAPTAVP were effectively improved by fluorescence resonance energy transfer (FRET) with PCBMB and attenuating the intramolecular charge transfer (ICT) after the addition of Ca(2+). The quantum yield and Φδ of PCBMB-BAPTAVP increased by about four and six times in comparison to those of BAPTAVP, respectively. The TP fluorescence imaging experiments indicated that the PCBMB-BAPTAVP system could effectively detect Ca(2+) in living cells with high sensitivity.